2016
DOI: 10.5296/ieb.v2i1.9626
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Variability and Manufacturing Sector Performance in Ghana: Evidence from Cointegration Analysis

Abstract: This study examined the effect of exchange rate variability on manufacturing sector performance in Ghana. Using time series data from the period 1986-2013 and employing the autoregressive distributed lag (ARDL) approach, the empirical results show that there exists both a short as well as long run relationship between exchange rate and manufacturing sector performance. Thus, in Ghana as the exchange rate appreciates, the manufacturing sector performance improves and as it depreciates, the sector is adversely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
1
5
1
Order By: Relevance
“…Firms with higher share of imported inputs are adversely affected from MUR depreciation in face of higher variable costs. The result is consistent with the finding of Abdul‐Mumuni (2016) who reported that appreciation of the real home currency led to an increase in manufacturing sector performance in Ghana. In Nigeria, Olufisayo & Adebayo (2015) and Omotola (2016) found positive but insignificant effect of fluctuation of exchange rate on manufacturing output while in Romania, Orhunbilge & Tas (2014) found mixed results in the short‐run and no long‐run relationship between exchange rate movements and manufacturing growth rate was observed.…”
Section: Manufacturing and Services Sectors Growth Modelssupporting
confidence: 92%
See 1 more Smart Citation
“…Firms with higher share of imported inputs are adversely affected from MUR depreciation in face of higher variable costs. The result is consistent with the finding of Abdul‐Mumuni (2016) who reported that appreciation of the real home currency led to an increase in manufacturing sector performance in Ghana. In Nigeria, Olufisayo & Adebayo (2015) and Omotola (2016) found positive but insignificant effect of fluctuation of exchange rate on manufacturing output while in Romania, Orhunbilge & Tas (2014) found mixed results in the short‐run and no long‐run relationship between exchange rate movements and manufacturing growth rate was observed.…”
Section: Manufacturing and Services Sectors Growth Modelssupporting
confidence: 92%
“…In the case of Nigeria, Olufisayo and Adebayo (2015) by making use of Vector Error Correction Model (VECM) over the time period 1986–2010, showed that, in the long‐run, depreciation had an expansionary effect on industrial production while in the short‐run no such relation was revealed by the data. More recently, Abdul‐Mumuni (2016) had applied the autoregressive distributed lag (ARDL) method to the Ghanaian time series data and found both a short‐run and a long‐run relationship between exchange rate and manufacturing output. In Ghana, an appreciation spurred manufacturing activities while depreciation slowed down output growth in the sector.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Specifically, Boateng (2019) focused on manufacturing sector in terms of financial performance and used return on assets and equity as a measure for manufacturing sectors performance whereas Abdul-Mumuni (2019) used manufacturing sectors percentage of Gross Domestic product (GDP) as a measure of manufacturing sectors performance. In this regard, the present study differs from studies by (see Boateng, 2019;Abdul-Mumuni, 2019) significantly on the effect of exchange rate fluctuations on the performance of manufacturing sectors in Ghana for at least a number of reasons and make at least two significant contributions. Firstly, we add to the scanty literature on the nexus between exchange rate fluctuation and manufacturing sectors performance in Ghana.…”
Section: Introductioncontrasting
confidence: 82%
“…Firstly, we add to the scanty literature on the nexus between exchange rate fluctuation and manufacturing sectors performance in Ghana. Secondly, the present study uses a relatively Economics Literature 2019(2): 133-147 doi: 10.22440/elit.1.2.4 current and larger sample period from 1990 to 2018 as compared to that of Abdul-Mumuni (2019) and Boateng (2019) that used 1986 to 2013 and 2009 to 2017. Thirdly we focus on different controls compared to the studies by (Abdul-Mumuni, 2019; Boateng, 2019) which includes: exchange rate, monetary policy rate, trade openness, and investment.…”
Section: Introductionmentioning
confidence: 99%
“…It is used in this model as the dependent variable because it can be regarded as a suitable proxy measure for the performance of the Nigerian manufacturing sector. It has also been used as a dependent variable in the literature by authors like Opaluwa et al (2010) and Abdul-Mumuni (2016). EXCH: As is embedded in economic theory, the Marshall Lerner conditions posit that if a country's sum of price elasticity for both import and export is greater than one, the BOP of such a country will improve with currency devaluation.…”
Section: Justification Of Variables In the Modelmentioning
confidence: 99%